Reception and flow of patients with mental disorders in Primary Care: experience report (Research, Society and Development, 2022)
Introduction: With the increase in the number of patients with mental disorders, the prevalence of care in health units rises. In this context, primary care professionals are responsible for welcoming and directing the flows of these users when necessary. Objective: To report the experience on the development and implementation of the booklet on reception and flows of these users as educational material for Primary Care Health professionals. Methods: This is a descriptive experience report of a resident of the Multiprofessional Family and Community Health Program (ESCS), where an intervention was carried out in a Health Unit located in the Federal District, following the assumptions of the Arch of Maguerez. Results and Discussion: Primary health care works as a gateway into the health system for users who have some psychological disorder, it is the privileged space for welcoming people who are in acute suffering and for building a longitudinal bond. It takes a constant exercise of self-assessment by professionals to avoid framing these users in stereotypes, always remembering that they are in a fragile situation and need to be taken care of, situations related to the field of mental health are among those that require the most effort from the team. for timely problem perception and decision making. Conclusion: The booklet has become a strategy that aims to carry out health education, which can be used as support material by any health professional assisting in the care of the user.